Analisis Yuridis Penggunaaan Smart Contracts Dalam Perjanjian Pembiayaan Bank - Fitrianto, Bambang; Fahri, Yusril; Barus, Wahyuda; Pratama, Satria Fadhil Wira (Sharia Journal and Education Center Publishing, 2025)
The development of information technology and the digitization of financial services have driven significant transformations in banking financing agreements, one of which is through the use of blockchain-based smart contracts. Smart contracts offer various advantages, such as process efficiency, transparency, certainty of agreement implementation, and automated contract execution without the need for third-party intervention. However, the application of smart contracts in bank financing agreements also raises a number of legal issues, particularly those related to the validity of agreements, legal evidence, the responsibilities of the parties, and customer protection in banking legal relationships. In the Indonesian legal system, regulations regarding smart contracts have not been specifically and comprehensively regulated, so their use in the banking sector has the potential to create legal vacuums and legal uncertainty. This study aims to analyze the use of smart contracts in bank financing agreements from a legal perspective, with an emphasis on their conformity with the principles of contract law and their legal implications in banking practice. The research method used is normative legal with a legislative and conceptual approach, through a review of banking regulations, contract law, and legal doctrines related to electronic contracts and blockchain technology. The results of the study indicate that, conceptually, smart contracts can be applied in bank financing agreements as long as they meet the requirements of a valid agreement and the applicable principles of contract law. However, the absence of specific legal regulations regarding smart contracts in Indonesian banking law emphasizes the need to establish an adaptive regulatory framework to ensure legal certainty, customer protection, and the security and sustainability of banking financing transactions in the digital era.